The Effectiveness of Problem Based-Learning Methods to Improve the Quality of Citizenship and Pancasila Learning in Elementary School - Rahayu, Aprillia Dian; Ramadan, Zaka Hadikusuma; Kuswanto, Cahniyo Wijaya (Universitas Nahdlatul Ulama Surabaya, 2023)
The problem with this research is that many students still need help understanding citizenship education and Pancasila learning. Many students need to be more active and able to think critically so they are less involved in learning interactions. This research aims to increase students' interest in learning about citizenship and Pancasila through problem-based learning methods. This research is experimental, with 32 grade 5 elementary school students as research subjects. Data collection tools use questionnaires and student learning outcomes. Data analysis used the t-distribution test. The research results showed an average increase of 28.12 points after the intervention or post-test. The data testing results answer the previously proposed hypothesis using the t distribution test with the core t count > t table (13.528 > 2.040), meaning Ho is rejected. These findings indicate that using problem-based learning methods increases students' interest and active learning in citizenship and Pancasila education subjects. This research contributes to solving the interest in studying citizenship and Pancasila education in elementary school education units, which were previously considered boring. Future research can test this in secondary education units.